Optimizing reading literacy through digital media-based deep learning: a case study at SB Kelana Jaya, Malaysia - Desi Ratna Tirtawati; Fitri Puji Rahmawati (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
This study examines the application of deep learning-based digital media to improve reading literacy in grade I students at SB Kelana Jaya, Malaysia. In the midst of the challenge of low literacy comprehension in students, the use of digital media such as Kahoot and Canva offers great potential to improve reading comprehension in a more interactive way. Using a qualitative approach with a case study design, this study collected data through observations, interviews, and literacy comprehension tests from principals, teachers, and students. The findings show that image and animation media significantly help students understand basic reading concepts, such as recognizing the alphabet, simple words, and sentences. The learning results showed that students who studied with digital media showed a better increase in reading literacy than those who used conventional methods. The integration of technology in creates a more adaptive and enjoyable learning atmosphere, which encourages active student engagement. This research highlights the urgency of implementing deep learning-based digital media in primary education to address literacy challenges and improve students' critical thinking skills in the context of 21st century education.